(untitled) (Itinera, 2025)
Transmedia artivism I4 in the media ecosystem: remediation, reappropriation and viralisation in the age of the produso Just as species adapt, coexist, and become extinct, media evolve according to the context of the moment. The research revolves around the leading role of the producer in eco-literacy processes to promote the defense of biodiversity. The development of innovative strategies —from an aesthetic and educommunicative perspective, based on the (post)digital ecosystem— can contribute to generating cutting-edge sociocultural expressions, while establishing a safe environment for accessing information that is generally incomprehensible, ineffective, or even inaccessible through traditional communicative, cultural, and pedagogical circuits. The study introduces a new methodology called «Transmedia Artivism i4», resulting from the convergence of research dissemination, innovation in educommunication, and media artivism. In the case of promoting citizen engagement for the conservation of biological diversity, practices of hybridization and media evolution contribute to strengthening the metacommunicative function of artistic and sociocultural expressions in hybrid environments, resulting from the combination of actions in physical and interconnective spaces. The current proposal advocates for the empowering potential of multiplatform experiential strategies based on reappropriation and co-creation to inform, raise awareness, and create action in the defense of biodiversity. Based on the observation of the influence of cyberactivism alongside culture jamming, performative, immersive, and guerrilla art, we will understand what this subcategory of media artivism consists of.